2016
DOI: 10.1016/j.ijleo.2016.02.067
|View full text |Cite
|
Sign up to set email alerts
|

A novel chiral nano structure for optical activities and negative refractive index

Abstract: We have numerically demonstrated a chiral nano structure based on double layered asymmetric Au film with hollowed-out split ring resonators on either side of the polyimide. This novel chiral nano structure can form multiple electric dipoles and magnetic dipoles in infrared and visible regions. And the interaction of these dipoles caused optical activities and multi-band negative refractive index. The appropriate geometric parameters are obtained through optimization and analysis of this structure. Circular dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…By simulating many variations of this structure, the system could be optimized, and also give insight into the underlying mechanism, due to the ability to visualize charge and current density within the material. By optimizing a hollowed out (inverted) split‐ring resonator structure, Jia et al later demonstrated a metamaterial in which LCP and RCP light had five and eight refractive index frequency bands respectively between 100 THz and 900 THz . In addition to using the simulations to optimize chirality, it was also shown that increased ring width and the size of the missing part of the ring (that gives the SRR its name) can blue‐shift these resonances.…”
Section: Chirality Parametersmentioning
confidence: 99%
“…By simulating many variations of this structure, the system could be optimized, and also give insight into the underlying mechanism, due to the ability to visualize charge and current density within the material. By optimizing a hollowed out (inverted) split‐ring resonator structure, Jia et al later demonstrated a metamaterial in which LCP and RCP light had five and eight refractive index frequency bands respectively between 100 THz and 900 THz . In addition to using the simulations to optimize chirality, it was also shown that increased ring width and the size of the missing part of the ring (that gives the SRR its name) can blue‐shift these resonances.…”
Section: Chirality Parametersmentioning
confidence: 99%
“…Until now, various strategies for the synthesis of carbon dots have been explored, like hydrothermal, microwave assisted, electrochemical carbonization, chemical ablation, etc. 12 The synthesis of chiroptical 13 nanoparticles is a great challenge nowadays as the conformation and molecular reorganization play a vital role in various elds, such as negative refractive materials, 14 chiro plasmonic high-sensitivity bioanalysis, 15 stereoselective reactions, chiral memory applications, 16 hyperbolic meta-surfaces, 17 chiral catalysis, 18 chiral sensors, 19 etc. There have been only a few reports on the synthesis of chiral quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…Aksu et al showed that by attaching a layer of highly stretchable low density polyethylene (LDPE) under the PDMS and Au nanorod layers, there could be a resonance peak shift up to 160 nm [94]. Soft polymers enable flexible optical metamaterials with new capabilities, such as negative refractive index [82,87,95], nonplanar SERS detectors [86,92] and molecular sensing [91,92,96].…”
Section: Polymersmentioning
confidence: 99%